Respuesta :

Answer:

√37

Step-by-step explanation:

the distance formula is

d = √(x2-x1)^2+ (y2-y1)^2

the x values are -4 and -5. the y values are 9 and 3. so you would plug in the x values to get -5 -(-4). double negatives make a positive, so you get -1. do the same with the y values to get -36. square those numbers to get 36 + 1 and keep the square root.

Answer:

[tex] \sqrt{37} [/tex]

Step-by-step explanation:

Use the distance formula:

The distance, d, between points (x1, y1) and (x2, y2) is

[tex] d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} [/tex]

Here you have points (-4, 9) and (-5, 3), so

[tex] x_1 = -4 [/tex]

[tex] y_1 = 9 [/tex]

[tex] x_2 = -5 [/tex]

[tex] y_2 = 3 [/tex]

[tex] d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} [/tex]

[tex] d = \sqrt{(-5 - (-4))^2 + (3 - 9)^2} [/tex]

[tex] d = \sqrt{(-5 + 4)^2 + (-6)^2} [/tex]

[tex] d = \sqrt{(-1)^2 + 36} [/tex]

[tex] d = \sqrt{1 + 36} [/tex]

[tex] d = \sqrt{37} [/tex]